2014
DOI: 10.1039/c3dt52661e
|View full text |Cite
|
Sign up to set email alerts
|

A facile one-pot reduction method for the preparation of a SnO/SnO2/GNS composite for high performance lithium ion batteries

Abstract: A SnO/SnO2/GNS composite with controlled oxidation states and composition has been prepared through simple one-pot reduction of an EG suspension of SnCl2 and graphene oxide. The as-prepared composite was characterized by XRD, FT-IR, XPS, SEM, TEM and BET. SnO and SnO2 nanoparticles are uniformly distributed on the surface of the graphene. Taking advantage of the high electron conductivity of graphene and the large theoretical capacity of SnO, this SnO/SnO2/GNS composite exhibits high charge/discharge capacity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 31 publications
5
36
1
Order By: Relevance
“…As shown in Figure 3a, only singular 3d 5 www.advelectronicmat.de ones reported for SnO 2 without indication of SnO phase. [15] Meanwhile only one peak of O 1s posited at 530.6 eV further confirmed the above conclusion ( Figure 3b). Hence, the XPS data indicated that this method is suitable for synthesis of SnO 2 films of high phase purity.…”
Section: Resultssupporting
confidence: 75%
“…As shown in Figure 3a, only singular 3d 5 www.advelectronicmat.de ones reported for SnO 2 without indication of SnO phase. [15] Meanwhile only one peak of O 1s posited at 530.6 eV further confirmed the above conclusion ( Figure 3b). Hence, the XPS data indicated that this method is suitable for synthesis of SnO 2 films of high phase purity.…”
Section: Resultssupporting
confidence: 75%
“…The CV curve for the first discharging process showed two broad reduction peaks at 0.15 and 0.65 V. The broad reduction peaks were due to the poor crystalline structure of the SnO x -carbon composite powders. The broad reduction peak observed at 0.65 V was associated with the formation of metallic Sn nanograins and amorphous Li 2 O through the reduction of SnO 2 and SnO [28,29]. The highly crystalline SnO 2 powders had a sharp reduction peak around 0.9 V in the first discharging process, as shown in Fig.…”
Section: Resultsmentioning
confidence: 87%
“…The reduction peak at 0.12V was attributed to the formation of Li x Sn alloys [29]. The strong broad oxidation peak at approximately 0.5 V in the first charging process was attributed to Li dealloying from Li x Sn [28]. The double peak located at 0.9/1.2 V observed during the second cycle was attributed to the partial reversibility reaction of Sn and SnO x [28,29].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…S5d) [30]. Whereas, for the SnO 2 @C hNFs, the minor peaks at 286.3 eV and 287.5 eV can be assigned to the oxidized carbon species such as carbon in C-O and carbonyl carbon C¼O, respectively [31]. Compared with SnO 2 @C hNFs, the C 1 s spectrum of SnO 2 @C@G hNFs contains one more peak (288.7 eV) corresponding to carboxylate carbon in O-C¼O [32].…”
Section: Morphology and Crystallization Of Sno 2 Hnfsmentioning
confidence: 97%